Enhancement of lysozyme crystallization using DNA as a polymeric additive - Zhang,B; Wang,Y; Thi,S; Toong,V; Luo,P; Fan,S; Xu,L; Yang,Z; Heng,JYY (Crystals, 2019)
This study reports the first experimental evidence of using DNA as a polymeric additive to enhance protein crystallization. Using three kinds of DNA with different molecular weights—calf DNA, salmon DNA, and herring DNA—this study showed an improvement in the success rate of lysozyme crystallization, as compared to control experiments, especially at low lysozyme concentration. The improvement of crystallization is particularly significant in the presence of calf DNA with the highest molecular weight. Calf DNA also speeds up the induction time of lysozyme crystallization and increases the number of crystals per drop. We hypothesized the effect of DNA on protein crystallization may be due to the combination of excluded volume effect, change of water’s surface tension, and the water competition effect. This work confirms predications of the potential use of DNA as a polymeric additive to enhance protein crystallization, potentially applied to systems with limited protein available or difficult to crystallize.